Nonconforming Finite Element Method for the Transmission Eigenvalue Problem. Issue 1 (11th October 2016) - Ji, Xia; Xi, Yingxia; Xie, Hehu
Abstract: In this paper, we analyze a nonconforming finite element method for the computation of transmission eigenvalues and the corresponding eigenfunctions. The error estimates of the eigenvalue and eigenfunction approximation are given, respectively. Finally, some numerical examples are provided to validate the theoretical results.